THE EFFORTS OF SOCIAL SERVICES AND POVERTY TREATMENT IN ADDRESSING STREET CHILDREN IN BANDUNG CITY - Nuradhawati, Rira (CosmoGov: Jurnal Ilmu Pemerintahan, 2020)
Living as street children is not a pleasant choice, because they are in conditions with no clear future, and their existence often becomes a "problem" for many parties, families, communities and the state. According to the 1945 Constitution, "abandoned children are cared for by country". By the Minister of Social Affairs Regulation Number 08 of 2012 Article 1 paragraph (8) concerning the Implementation of social welfare is a directed, integrated and sustainable effort carried out by the Government, regional government and the community in the form of social services to meet the basic needs of every citizen. which includes social rehabilitation, social security, social empowerment, and social protection. This study aims to obtain a comprehensive picture of how Dinsosnangkis City of Bandung's efforts to deal with street children. This research uses a descriptive qualitative approach. The results showed that in the context of policy content and the implementation of human and financial resources, it is very influential on the achievement of policy objectives and resource factors, especially financial, in this case, the budget becomes an obstacle in the implementation of Dinsonsnangkis policy in dealing with street children in Bandung City.